INTERNATIONALIZATION EFFORTS AMONG MALAYSIAN PRIVATE UNIVERSITIES - Ramanathan, Santhi (International Business Education Journal, 2011)
Over the last several decades, globalization and internationalization have changed the landscape and method of acquiring and sharing the knowledge at the higher education level worldwide. Along with this, international activities of most universities have expanded in volume, scope and complexity. In many ways the Malaysian higher education system particularly private higher education mirrors the global higher education system. Many studies were conducted at various levels (institutional, national and international) in order to cultivate a reliable framework for Malaysian higher education especially the university education system to realign their structure and mission towards international standards. In the context of the Malaysian private higher education sector, the private universities role is considered vital in adapting to internationalization policies and strategies. This study addresses the concern whether Malaysian Private Universities (MPUs) have internationalized as much as they have declared through their international strategic intents or mission statements. In addressing the above issue, cluster analysis was adapted as to explore MPU’s status on the internationalization continuum. This research provides a better understanding on the performance of the Malaysian private universities that embrace internationalization.